Marketing research of the range of medicinal products based on salts of natural origin - O. O. Saliy; O. P. Baula; K. Y. Melesh; G. I. Kuzmina (Фармацевтичний журнал, 2022)
As a source of supply of a balanced complex of salts in pharmaceutical practice, sea water (MW), sea salt (MS), obtained by the method of ordinary evaporation, or salt solutions made from standardized raw materials are used. Deep seawater (SW), typically pumped from depths greater than 200 m, contains a wealth of trace elements, including magnesium, calcium, potassium, chromium, selenium, zinc, and vanadium. Due to this, SW has the potential of a source and raw material for the creation of medicinal products for human health.